Epstein barr virus IgG and EBER-1 in Burkitt’s lymphoma children at a referral hospital in western Kenya - Ndede, Isaac (Pan Afr Med J, 2019)
Burkitt's lymphoma (BL) is a frequent childhood B cell non-Hodgkin's lymphoma (NHL) in equatorial Africa associated with infections. Chronic Epstein Barr virus (EBV) infections can lead to host immune stimulation that may trigger genetic translocation(s), neoplastic transformation and proliferation of B cells. We determined EBV immunoglobulin G (IgG) in sera from participants and EBER-1 in tumour sections in confirmed BL cases at Moi Teaching and Referral Hospital (MTRH). A cross sectional study of children with clinical and histology diagnosis of NHL from whom BL status were confirmed by immunohistochemistry (IHC) was carried out. Epstein Barr virus IgG in sera was determine using Enzyme-linked immunosorbant assay, IHC for EBER-1 and MYC protein in tumour sections. Demographic and clinical information were obtained from questionnaires and hospital files respectively. Ninety three percent of sera were EBV IgG positive of which 31.7% were confirmed as BL. All jaw BL tumours and 86.7% of BL tumours carried EBER-1 antigen. Odds ratio of EBER-1 positive was 1.39, 95% CI: 0.16-12.19 in BL tumours regardless of age or gender. EBV infection among the study participants may be associated with BL, however, EBER-1 and MYC negative in BL tumours suggest alternative BL pathogenesis or variant.